A Novel Hollow-Fiber Membrane Embedded Co-axial Microdevice for Simultaneous Extraction and Stripping. Issue 1 (2nd January 2020) - Yan, Zifei; Du, Chencan; Chen, Yuchao; Luo, Guangsheng
ABSTRACT: How to realize multistage liquid-liquid extraction in a single microdevice is a big challenge in micro-separation processes. No simple solution has been presented until now. In this work, we designed a hollow-fiber membrane-embedded co-axial microdevice with a controllable transmembrane pressure to realize a multistage extraction process successfully. Using the extraction of phenol as a model system, the steady liquid-liquid-liquid three-phase flow of the feed, extractant, and back-extractant was realized in the designed microdevice. By precisely controlling the pressure of the tube side, the extractant was separated from the feed in situ and passed into the shell side to contact with the back-extractant directly. In this way, both of the extraction yield and stripping yield reached 95%. And by introducing a transmembrane pressure with periodic oscillation, five theoretical stages were successfully achieved within 3 min residence time in the single microdevice. This technology may open a new area for microfluidic applications.